Method for detecting pipeline spatial attitude using point cloud alignment - Li, Pengfei; Zhang, Qing; Wang, Xiankang; Zhao, Tianren; Wang, Yaze (Measurement : journal of the International Measurement Confederation, 2023)
•A new method for detecting the spatial attitude of pipeline welding based on point cloud registration.•We propose a coarse registration algorithm based on the axial line of pipeline point clouds to help facilitate the alignment process.•Providing guidance on welding posture prior to welding to minimize rework situations. This paper introduces a new method for detecting the spatial attitude of pipeline welding based on point cloud registration. The method aligns the measured point cloud of the pipeline with the CAD model point cloud using point cloud registration and guides the pipeline adjustment accordingly. This automated measurement method has resolved the inefficiencies and potential for rework that can arise from manual instrument operation during pipeline pose detection, and has subsequently improved detection efficiency and accuracy. In addition, we propose a coarse registration algorithm based on the axial line of pipeline point clouds to help facilitate the alignment process. We conducted simulation experiments using 3D CAD models, which demonstrated that our coarse registration algorithm outperformed the other three compared methods in terms of accuracy. The simulation experiments also proved that the absolute value of the overall method's relative error was less than 0.1%.